Situation Report: Romania, 9 August 1963 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania Signs Test Ban Treaty Romanian Broadcasts Free of Jamming; Hsinhua [Xinhua] Comments "Probleme Economice" on Equalization of Economic Level of Comecon Member Countries